2017
DOI: 10.1073/pnas.1618475114
|View full text |Cite|
|
Sign up to set email alerts
|

Global long-range transport and lung cancer risk from polycyclic aromatic hydrocarbons shielded by coatings of organic aerosol

Abstract: Polycyclic aromatic hydrocarbons (PAHs) have toxic impacts on humans and ecosystems. One of the most carcinogenic PAHs, benzo(a)pyrene (BaP), is efficiently bound to and transported with atmospheric particles. Laboratory measurements show that particle-bound BaP degrades in a few hours by heterogeneous reaction with ozone, yet field observations indicate BaP persists much longer in the atmosphere, and some previous chemical transport modeling studies have ignored heterogeneous oxidation of BaP to bring model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
228
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(254 citation statements)
references
References 54 publications
4
228
2
2
Order By: Relevance
“…Further, they could disable or reduce the aerosol-induced transport of certain species, which cannot be taken up by particles after becoming highly viscous, or, conversely, enable or enhance the aerosol-induced transport of species, which were locked in before becoming highly viscous. Zelenyuk et al (2012) and Shrivastava et al (2017) suggested that long-range transport of PAHs trapped in highly viscous SOA may contribute to unexpectedly high particle-bound PAH concentrations in remote regions. In addition, there have been suggestions that PAHs may be trapped irreversibly within the soot matrix (Fernández et al, 2002), but we do not further discuss this mechanism here.…”
Section: Atmospheric Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they could disable or reduce the aerosol-induced transport of certain species, which cannot be taken up by particles after becoming highly viscous, or, conversely, enable or enhance the aerosol-induced transport of species, which were locked in before becoming highly viscous. Zelenyuk et al (2012) and Shrivastava et al (2017) suggested that long-range transport of PAHs trapped in highly viscous SOA may contribute to unexpectedly high particle-bound PAH concentrations in remote regions. In addition, there have been suggestions that PAHs may be trapped irreversibly within the soot matrix (Fernández et al, 2002), but we do not further discuss this mechanism here.…”
Section: Atmospheric Outlookmentioning
confidence: 99%
“…Unlike biogenic films, for which no RH threshold was observed, anthropogenic films exhibited increased evaporation rates above RH ∼ 20-30 %. Diffusion limitations for oxidants and organic molecules could also lead to the trapping of VOCs, such as harmful polycyclic aromatic hydrocarbons (PAHs) in the aerosol phase and protect them from oxidation, thereby facilitating their long-range transport (Shrivastava et al, 2017). In a study of evaporation rates, Abramson et al (2013) estimated the condensed-phase diffusivity (D c ) of pyrene, a PAH, contained in freshly produced α-pinene SOA as D c = 2.5×10 −17 cm 2 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Note that this relation is not accurate for predicting the bulk diffusivity of water and small molecules and it may also underestimate the diffusivity of organic molecules in a highly viscous matrix by a few orders of magnitudes (Champion et al, 2000;Shiraiwa et al, 2011;Power et al, 2013;Marshall et al, 2016;Bastelberger et al, 2017;Reid et al, 2018). The particle phase state, viscosity, and bulk diffusivity have been shown to affect the gas uptake and chemical transformation of organic compounds due to the kinetic limitations of bulk diffusion Abbatt et al, 2012;Zhou et al, 2013;Slade and Knopf, 2014;Arangio et al, 2015;Davies and Wilson, 2015;Wang et al, 2015;Berkemeier et al, 2016;Marshall et al, 2016;Liu et al, 2018;Pratap et al, 2018;Zhang et al, 2018), which may facilitate the long-range transport of organic compounds embedded in viscous or glassy particles (Shrivastava et al, 2017b;Mu et al, 2018). Molecular motion can be hindered in a highly viscous matrix, slowing down photochemical reactions in particles (Lignell et al, 2014;Hinks et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, the lifetime of BrC is dependent on other factors related to aerosol oxidation and phase state, which we will discuss next. In a recent study, Shrivastava et al (2017) reported observations of an enhanced lifetime for PAHs due to the aerosol phase state during transport. The aerosol solid phase state has been shown to decrease the rate of photodegradation (Lignell et al, 2014;Hinks et al, 2015) and water diffusivity (Berkemeier et al, 2014).…”
Section: Molecular Formula Aromaticity and Brown Carbonmentioning
confidence: 99%